Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13075-020-2122-5
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity versus poor response to tumour necrosis factor inhibitors in rheumatoid arthritis: a retrospective cohort study

Abstract: Background: With advancement in the treatment options of rheumatoid arthritis (RA), optimising the outcomes of difficult-to-treat patients has become increasingly important in clinical practice. In particular, insensitivity to first-line biologic disease-modifying anti-rheumatic drugs (bDMARD) is becoming a significant problem because it may decrease the treatment adherence of patients. This study aimed to compare RA patients with an insensitivity and those with a poor response to initial treatment with tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…The latent class analyses also revealed that about one tenth of patients in both the EORA and non-EORA elderly groups showed little response to a b/tsDMARD (Group 3 in Figure 4). This is compatible with our previous study that demonstrated that a difference might exist between insensitivity and poor response to TNFis among b/tsDMARD-naïve patients (21). The results of the present study further suggest that the same might be true for patients treated with other b/tsDMARDs and for patients who are not naïve to b/tsDMARDs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The latent class analyses also revealed that about one tenth of patients in both the EORA and non-EORA elderly groups showed little response to a b/tsDMARD (Group 3 in Figure 4). This is compatible with our previous study that demonstrated that a difference might exist between insensitivity and poor response to TNFis among b/tsDMARD-naïve patients (21). The results of the present study further suggest that the same might be true for patients treated with other b/tsDMARDs and for patients who are not naïve to b/tsDMARDs.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously reported that different patterns of treatment response might exist among b/tsDMARD-naïve RA patients treated with TNFis (21). Therefore, we hypothesized that a similar pattern might be observed among the present patients.…”
Section: Latent Class Analysissupporting
confidence: 51%
“…A large proportion of patients show a poor response to DMARDs or biological agents (94,95). Drug treatment can alter serum metabolite levels in RA (96)(97)(98)(99).…”
Section: Identifying Biomarkers Of Ra Using Metabolomicsmentioning
confidence: 99%
“…The FIRST registry is a multi-institutional cohort of RA patients treated with b/tsDMARDs, established by the University of Occupational and Environmental Health, Japan and its multiple a liated hospitals. Detail of the cohort is available in other articles [5][6][7][8][9]. In this registry, all registered RA patients were enrolled in a long-term observational study at the point of new or switch-prescription of b/tsDMARDs.…”
Section: Data Sourcementioning
confidence: 99%